The STK33-linked SNP rs4929949 is associated with obesity and BMI in two independent cohorts of Swedish and Greek children. - Mathias Rask-Andersen (Public Library of Science (PLoS), 2013)
Recent genome wide association studies (GWAS) have identified a locus on chromosome 11p15.5, closely associated with serine/threonine kinase 33 (STK33), to be associated with body mass. STK33, a relatively understudied protein, has been linked to KRAS mutation-driven cancers and explored as a potential antineoplastic drug target. The strongest association with body mass observed at this loci in GWAS was rs4929949, a single nucleotide polymorphism located within intron 1 of the gene encoding STK33. The functional implications of rs4929949 or related variants have not been explored as of yet. We have genotyped rs4929949 in two cohorts, an obesity case-control cohort of 991 Swedish children, and a cross-sectional cohort of 2308 Greek school children. We found that the minor allele of rs4929949 was associated with obesity in the cohort of Swedish children and adolescents (OR = 1.199 (95%CI: 1.002-1.434), p = 0.047), and with body mass in the cross-sectional cohort of Greek children (β = 0.08147 (95% CI: 0.1345-0.1618), p = 0.021). We observe the effects of rs4929949 on body mass to be detectable already at adolescence. Subsequent analysis did not detect any association of rs4929949 to phenotypic measurements describing body adiposity or to metabolic factors such as insulin levels, triglycerides and insulin resistance (HOMA).